The Influence of Body Structure and Eye-Hand Coordination on Upper Passing Ability in Volleyball Games - Syahruddin Syahruddin; Muhammad Syahrul Saleh; M. Sahib Saleh (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
The cause is not optimal due to non-bio motor factors, namely inadequate body structure, and bio motor factors, namely poor hand-eye coordination. This study aims to determine whether or not there is an effect of body structure on the ability of pass over, to determine whether there is an effect of eye coordination on the ability to passing-over and to determine whether there is an influence of body and eye-hand coordination on the ability to pass over. This type of research is descriptive correlational by involving the independent variables (independent) consisting of body structure and eye-hand coordination, while the controlling variable is the ability to pass. The research sample was students of SMP Negeri 27 Makassar with a total of 30 people drawn by random sampling. The research instrument used an upper passing test, measurement of body structure by measuring height, weight and arm length, and eye-hand coordination with a chess pass test. The results showed that there was a significant effect on the body's upper passing ability (p<0.05), there was a significant structural effect of eye-hand coordination on the upper-passing ability, and there was a jointly significant effect of body structure and eye coordination on upper passing ability (p<0.05).